In situ tailoring of superconducting junctions via electro-annealing. Issue 4 (10th January 2018) - Lombardo, Joseph; Jelić, Željko L.; Baumans, Xavier D. A.; Scheerder, Jeroen E.; Nacenta, Jorge P.; Moshchalkov, Victor V.; Van de Vondel, Joris; Kramer, Roman B. G.; Milošević, Milorad V.; Silhanek, Alejandro V.
Abstract : Controlled electro-annealing allowed the in situ formation of a tunable superconducting weak link in Nb nanoconstrictions. Abstract : We demonstrate the in situ engineering of superconducting nanocircuitry by targeted modulation of material properties through high applied current densities. We show that the sequential repetition of such customized electro-annealing in a niobium (Nb) nanoconstriction can broadly tune the superconducting critical temperature T c and the normal-state resistance R n in the targeted area. Once a sizable R n is reached, clear magneto-resistance oscillations are detected along with a Fraunhofer-like field dependence of the critical current, indicating the formation of a weak link but with further adjustable characteristics. Advanced Ginzburg–Landau simulations fully corroborate this picture, employing the detailed parametrization from the electrical characterization and high resolution electron microscope images of the region within the constriction where the material has undergone amorphization by electro-annealing.